MOBILE INTERNET-BASED LEARNING TO CULTIVATE STUDENTS’ SPEAKING SKILL DURING CORONAVIRUS PANDEMIC - Ida Ayu Made Sri Widiastuti; Ida Bagus Nyoman Mantra; Heru Sukoco (Unmas Press, 2020)
Coronavirus pandemic has been spreading in Indonesia and influences the way of Indonesian life. In the education sector, the coronavirus pandemic has forced teachers to conduct all the learning activities from home. The present study dealt with teaching speaking skill through mobile internet-based learning during the coronavirus pandemic where all students had to learn from their own home. The present online learning conducted in two cyclic sessions by making use of pre-test and post-test research design with descriptive and quantitative analysis to collect the required data. The grand mean figures for the first cycle and second cycle showed convincing findings since the mean figure of the initial reflection is much lower than the corresponding mean figures obtained for each session. Therefore mobile internet-based learning is considered to be an effective way of learning during coronavirus pandemic in Indonesia.